2016
DOI: 10.12968/hmed.2016.77.9.530
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic cervical spine fractures in the adult

Abstract: This article reviews fractures of the cervical spine, highlighting the pertinent goals of initial management, the indications for different imaging modalities and the different fracture patterns. Basic principles of management of these different fracture patterns are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…This is the same as what reported in the same study [11]. We found that the most common age group was (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The sekhar paper found that the incidence of cervical spine trauma was highest in the age group of 21-30 years followed by 31-40 [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is the same as what reported in the same study [11]. We found that the most common age group was (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The sekhar paper found that the incidence of cervical spine trauma was highest in the age group of 21-30 years followed by 31-40 [11].…”
Section: Discussionsupporting
confidence: 89%
“…While theoretical and experimental animal studies showed that early intervention may give advantage for spinal cord injuries with cervical fractures, no clinical studies have showed this yet. Experts advised to interfere with in 8-24 hours [28,29]. And this goes with what we found.…”
Section: Discussionsupporting
confidence: 79%
“…ABBREVIATIONS: AI ¼ artificial intelligence; ASiR ¼ adaptive statistical iterative reconstruction; DSS ¼ decision support system; CSFx ¼ cervical spinal fractures C ervical spinal fractures (CSFx) are devastating injuries that can cause severe morbidity and mortality from damage to the enclosed spinal cord, the craniocervical junction, and cervical vasculature. 1 Failure of the osseous spinal column can lead to instability and impingement of the underlying spinal cord; 2 therefore, timely identification and stabilization of CSFx are crucial to prevent further disability. 1,3 In the acute clinical setting, NCCT of the cervical spine is the recommended method for detecting CSFx; 4 however, with diagnostic imaging volumes dramatically increasing, 5,6 these increased imaging volumes place a burden on radiologists who must maintain diagnostic accuracy and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…1 The goals, indications, approaches, and techniques for the treatment of cervical injuries are well established. 2 However, therapeutic tools used during surgery depend on their availability.…”
Section: Introductionmentioning
confidence: 99%